A Comparison of Fast Spin-Echo, Fluid-Attenuated Inversion-Recovery, and Diffusion-Weighted MR Imaging in the First 10 Days after Cerebral Infarction - Ricci, Peter E. (AJNR Am J Neuroradiol, 1999)
BACKGROUND AND PURPOSE: Echo-planar diffusion-weighted and fluid-attenuated inversion-recovery (FLAIR) imaging have both proved valuable for detecting acute ischemic infarcts, but little is known about the value of diffusion-weighted imaging beyond the acute infarct period. Furthermore, no direct comparison of the techniques has been published. We compared the diagnostic utility of diffusion-weighted, FLAIR, and T2-weighted fast spin-echo (FSE) imaging for detecting cerebral infarctions up to 10 days old. METHODS: FSE, FLAIR, and diffusion-weighted MR sequences were obtained prospectively over a 6-month period in 212 patients with suspected cerebral infarctions. Seventy patients with nonhemorrhagic ischemic infarcts less than 10 days old whose symptoms lasted longer than 48 hours were identified. The three sequences were compared for detectability and conspicuity of abnormalities that correlated with the neurologic deficit. RESULTS: Seventy-two symptomatic infarcts were found in the 70 patients. Diffusion-weighted imaging detected 70 (97%), FLAIR, 69 (96%), and FSE, 64 (89%) of the 72 lesions. Only the difference between diffusion-weighted and FSE imaging approached statistical significance. There was no difference in the number of lesions detected in the patients imaged 48 hours or more after infarction. Lesion conspicuity on diffusion-weighted images was judged superior to that on FSE and FLAIR images in 55 (77%) and 47 (67%) of the cases, respectively. FLAIR images were judged superior to FSE in 34 (48%) of the cases. CONCLUSION: Diffusion-weighted images showed more infarcts than FLAIR and FSE images, and FLAIR images showed more than FSE images, but the differences were not statistically significant. Lesion conspicuity, however, was consistently better on diffusion-weighted images than on either FLAIR or FSE images throughout the 10-day period. Acquisition of diffusion-weighted images in the late acute and subacute periods after ischemic cerebral infarction appears to be beneficial.